2012
DOI: 10.1080/10610278.2012.695790
|View full text |Cite
|
Sign up to set email alerts
|

ZnII and PbII coordination chemistry of 2,6-bis(1,2,3-triazol-4-yl)pyridine (clickate) and the metal ion-dependent emission of ‘clickate’–appended anthracene

Abstract: 2012) Zn II and PbII coordination chemistry of 2,6-bis(1,2,3-triazol-4-yl)pyridine (clickate) and the metal ion-dependent emission of 'clickate'-appended anthracene, Supramolecular Chemistry, 24:9, 696-706,The effect of metal coordination of 2-(1-(9-anthryl)methyl-1,2,3-triazol-4-yl)-6-(1-n-octyl-1,2,3-triazol-4-yl)pyridine (2) on the emission of the appended anthryl group was investigated in acetonitrile. The tridentate 2,6-bis(1,2,3-triazol-4-yl)pyridyl ligand included in 2 is referred herein as 'clickate'. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Similar rhodamine spirolactam systems with different substituents have recently been reported. 35,43,44 The pyridyl and triazolyl groups are in a typical transoid arrangement 45 with a dihedral angle of 13.6° for minimizing the dipole interactions between the two heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Similar rhodamine spirolactam systems with different substituents have recently been reported. 35,43,44 The pyridyl and triazolyl groups are in a typical transoid arrangement 45 with a dihedral angle of 13.6° for minimizing the dipole interactions between the two heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that magnetic exchange through the hydrogen bonds was the most likely pathway. 114 Both Zhu and Dash briefly mentioned Cu(II) quenching the florescence emission of ligands 5, 26 115 as well as compound 27. 116 However, these systems will be discussed in more detail below in relation to their fluorescence emission enhancement upon interaction with Zn(II).…”
Section: Coppermentioning
confidence: 99%
“…Herein, we report the crystal structure of the title compound. In the title compound, all the bond lengths are within normal ranges [5], similar to its two analogues [6,7]. One Zn(II) is …”
Section: Discussionmentioning
confidence: 81%